In vitro antimicrobial, antioxidant, cytotoxicity and GC-MS analysis of Mazus goodenifolius - Riaz, Muhammad; Rasool, Nasir; Bukhari, Iftikhar Hussain; Shahid, Muhammad; Zubair, Muhammad; Rizwan, Komal; Rashid, Umer (MDPI, 2012)
The antimicrobial, antioxidant and cytotoxic properties of Mazus goodenifolius (Hornem.) Pennell essential oil, methanol extract and some solvent-extracted subfractions of the latter were appraised. A qualitative, quantitative analysis of the classes of phytochemicals in the various fractions and GC-MS analysis of the essential oil was carried out. The activity of the plant extract and various subfractions against selected bacterial (Pasturella multocida, Escherichia coli, Bacillus subtilis and Staphylococcus aureus) and fungal strains (Aspergillus niger, Aspergillus flavus, Alternaria alternata and Rhizopus solani) was evaluated. The antioxidant activity was assayed using the DPPH radical scavenging and % inhibition of linoleic acid peroxidation tests. In the DPPH radical scavenging test the IC50 values ranged from 7.21 to 91.79 µg/mL, and in the latter the range of % peroxidation inhibition was 35.42–93.48%. Protective effects of the absolute methanol extract, which had the highest content of phenolics and flavonoids, against H2O2 induced oxidative damage in plasmid pBR322 DNA was also evaluated, and it was found to offer some protection at the highest tested dose (1,000 µg/mL). Finally the cytotoxicity of the plant extract, fractions and essential oil was analyzed by examining haemolytic activity against human blood erythrocytes (RBCs), whereby the % lysis of RBCs was found to be in the range of 1.65 to 4.01%.